Sosial Media, Bisnis Kuliner dan Pandemi Covid-19 - Jessica Leofitri (Universitas Medan Area, 2021)
This study aims to see how the use of information technology, especially social media and online applications, supports the emergence of this business. The research method in this study uses a qualitative approach and uses a phenomenological methodology through in-depth interviews to see the experience of one of the home-based online business entrepreneurs who built their business during the Covid 19 pandemic. The informant in this study was a 32-year-old woman with a bachelor's degree in economics. informants know quite a lot about marketing techniques. The results show that the most important use of social media is to create electronic word of mouth which is the backbone of the success of home-based online business marketing. Age is also a determining factor in operating an online-based business using this information and communication technology. So, it can be concluded that the use of communication information technology is the main key to the creation of online home-based businesses that were born during the Covid 19 pandemic. Social media, online motorcycle taxi applications, e-commerce are very helpful for home-based online businesses to run their business during the Covid pandemic. 19.